Patterns of Young Children’s Number Sense Development as Assessed by How Many Hidden Game - Connie Cassy Ompok; Brian Doig; Maria Tambagas (2018)
Using games as a context for assessing children’s mathematical abilities is not unusual, but this study investigated the potential of games designed specifically for the purpose of assessment. Children in prior-to-school settings in Sabah, Malaysian Borneo, were exposed to a range of such games, including the how many hidden game, which focuses on number sense, which is the subject of this paper. Children’s responses while playing the game were recorded, and we report the range of successful responses to the game, as well as the age of the children involved.